2022
DOI: 10.1186/s12902-022-00945-4
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting CLT in PTC is an independent predictor of tumor aggressiveness for patients aged under 55: a retrospective analysis of 635 patients

Abstract: Background The study was aimed at investigating the potential role of chronic lymphocytic thyroiditis (CLT) in papillary thyroid cancer (PTC) aggressiveness for patients aged below 55, as well as to figure out factors influencing potential recurrence risk in different age groups. Methods A total of 635 adult patients were retrospectively analyzed. 188 patients were diagnosed with coexistent CLT and the remaining 447 were classified as non-CLT. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…The results obtained in this study related to the aggressiveness of PC in patients with HT were also observed by other authors [21,30,31]. Among these, several pathologic features of aggressiveness have also been observed in a study conducted of patients with HT associated with PC in areas of endemic goiter with iodine deficiency, in which the PC variant constituted 74.1% of thyroid cancer [54].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results obtained in this study related to the aggressiveness of PC in patients with HT were also observed by other authors [21,30,31]. Among these, several pathologic features of aggressiveness have also been observed in a study conducted of patients with HT associated with PC in areas of endemic goiter with iodine deficiency, in which the PC variant constituted 74.1% of thyroid cancer [54].…”
Section: Discussionsupporting
confidence: 86%
“…However, it is a matter of controversy whether the behavior of the carcinomas is more aggressive when the two diseases are associated with thyroid cancer. It has been observed that the appearance of metastatic lesions during follow-up is more frequent in patients with PC/GD [34][35][36][37] and PC/HT [21,22,30,31] than in PC patients without these autoimmune diseases. However, other studies have observed no difference in the outcome in the patients with or without GD and HT [15,38,39], while others have suggested that the two diseases may be factors of a more favorable disease course [3,8,[10][11][12][13]20,40,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation within the thyroid gland, as observed in CLT, may create an environment conducive to the initiation or progression of thyroid cancer [5,13,14]. However, the exact relationship between inflammation and the development of DTC is complex and requires further investigation to determine the mechanisms involved and the extent of their influence on cancer progression [15,16]. Moreover, data on the impact of the CLT on the clinical and pathological parameters of DTC are ambiguous [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%